Fatty acids profile of Serra da Estrela PDO cheeses and respective atherogenic and thrombogenic indices - Lima, M.J. Reis (2020)
This study aims to determine the physicochemical and fatty acids composition of Serra da Estrela cheese (SEC), as well as health-related lipid indices, like the atherogenic and thrombogenic indices, and to evaluate the influence of producer, geographical origin and production date. Design/methodology/approach – All 24 SEC produced between November 2017 and March 2018 were collected at selected certified producers and analyzed by NIR spectrophotometer and by GC. Data were statistically evaluated by chemometric tools. Findings – In all evaluated SEC, 23 fatty acids were quantified. Cheese origin influenced nutritional and health-related lipid indices). The cheeses were characterized by a relative high abundance of saturated fatty acids (67-76%), followed by a medium content of monounsaturated fatty acids (17-25%) and by low level of polyunsaturated fatty acids (5-7%). A putative positive association between cheese consumption and healthy lipid indices could be reached. Practical implications – The contents of some medium and long chain fatty acids as well as of nutritional and health indices were influenced by cheese producer, geographical origin and production date pointing out the need for standardizing production procedures. Social implications – The SEC plays a key role in the local economy, being an endogenous product with unique sensory characteristics and nutritional potential, for which the knowledge of the lipids profile and health indices is of utmost relevance. Originality/value – SEC is an iconic Portuguese cheese with Protected Designation of Origin. Based on the results, like health-related lipid indices, evaluated for the first time, a positive association between cheese consumption and healthy lipid indices could be envisaged.